Minimally Invasive Interventional Management of Gastric Outlet Obstructions - Zhou, Wei-Zhong; Yang, Zheng-Qiang (Digestive Disease Interventions, 2018)
Gastric outlet obstruction (GOO) is a clinical consequence of any disease that produces intrinsic or extrinsic obstruction of the pyloric channel or duodenum. The most common symptoms of GOO include nausea, vomiting, abdominal pain, and weight loss. Traditionally, surgery is regarded as the standard treatment modality. However, with the development of mini-invasive technologies, fluoroscopic or endoscopic stenting and balloon dilatation have become the mainstream of the therapies. The initial recommended treatment for malignant GOO is self-expanding metal stent placement. The stent can be classified into covered and uncovered stent according to whether it is coated with a membrane. Covered stent seems to have longer stent patency, while uncovered stent has the advantage of a lower migration rate. Regarding the etiology of benign GOO, peptic ulcer disease and corrosive injury are the two main reasons. Balloon dilatation is a simple and convenient way to treat the benign GOO. Stent placement has recently been reported for the treatment of benign GOO; however, it needs further more studies to verify its effect. This article presents a concise review of current fluoroscopic or endoscopic stenting practice for malignant GOO and balloon dilatation or stenting for benign GOO.
Keywords: gastric outlet obstruction; stent; balloon dilatation; surgical gastrojejunostomy